The peacefulness gene promotes aggression in Drosophila - Ramin, Mahmoudreza (Mol Brain, 2019)
Natural aggressiveness is commonly observed in all animal species, and is displayed frequently when animals compete for food, territory and mating. Aggression is an innate behaviour, and is influenced by both environmental and genetic factors. However, the genetics of aggression remains largely unclear. In this study, we identify the peacefulness (pfs) gene as a novel player in the control of male-male aggression in Drosophila. Mutations in pfs decreased intermale aggressiveness, but did not affect locomotor activity, olfactory avoidance response and sexual behaviours. pfs encodes for the evolutionarily conserved molybdenum cofactor (MoCo) synthesis 1 protein (Mocs1), which catalyzes the first step in the MoCo biosynthesis pathway. Neuronal-specific knockdown of pfs decreased aggressiveness. By contrast, overexpression of pfs greatly increased aggressiveness. Knocking down Cinnamon (Cin) catalyzing the final step in the MoCo synthesis pathway, caused a pfs-like aggression phenotype. In humans, inhibition of MoCo-dependent enzymes displays anti-aggressive effects. Thus, the control of aggression by Pfs-dependent MoCo pathways may be conserved throughout evolution. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13041-018-0417-0) contains supplementary material, which is available to authorized users.